Dampak Teknologi Terhadap Etos Kerja Pendidik dan Peserta Didik dalam Pendidikan Islam di SMPN 2 Sijunjung - Febrinal, Dian; Bustamam, Risman; Saputra, Septia Irnanda; Irwadi, Hermen (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze the impact of technology usage on the work ethic of educators and students in Islamic Education learning at SMPN 2. The approach used is qualitative research with a case study design, involving data collection through in-depth interviews, participatory observation, and document analysis. The results of the study show that the use of technology has both positive and negative impacts on the work ethic of both parties. For educators, technology facilitates access to teaching materials, improves time efficiency, and enriches teaching methods, which leads to an increase in motivation and commitment to performing teaching duties. However, the main challenge faced is how to ensure that technology does not diminish the moral and spiritual values that are the core of Islamic Education. For students, technology enhances motivation and engagement in learning, provides flexibility in studying, and makes access to teaching materials easier. Nevertheless, there is a tendency for students to be distracted by other technological features, which can reduce their focus on religious studies. This study also finds that technology can be optimized by designing its use in a planned and directed manner, both for educators and students, so that it remains in line with the objectives of Islamic Education, which emphasizes character building and morality.